Mampukah Digital Literacy Memengaruhi Minat Menggunakan Aplikasi Akuntansi Berbasis Smartphone Bagi UMKM? - Puji Rahayu; Imarotus Suaidah; Zahra Devian Wardani (Universitas Winaya Mukti, 2022)
There has been a shift in consumer behavior followed by entrepreneur behavior due to the impact of the Covid-19 pandemic and advances in technology. Entrepreneurs must have records so they can know the progress of the business they are running. In order to record neatly and save capital, you can take advantage of existing accounting applications on smartphones in finding information related to the ease of use of some of these accounting applications through digital literacy. This research has a purpose to analyze whether digital literacy can influence the interests of MSMEs to use smartphone-based accounting applications in their business activities. This type of research is descriptive quantitative. MSME entrepreneurs in the city of Kediri are the population in this research and use 40 respondents as a sample with a sampling technique using a simple rando sampling method. Simple linear regression is a method used to analyze data. The research results show that there is a significant influence between digital literacy with MSME’s interest in using smartphone-based accounting applications. The implications of the results of this research apart from for SMEs that can be efficient in managing capital, the achievement of the government's program of upgrading MSMEs has also materialized. Suggestions for future researchers are even more extended for sampling.